Socio-demographic Status and Psychiatric Morbidity of Suicide Attempters in a Tertiary Care Hospital of Bangladesh (Journal of Rangpur Medical College, 2023)
Background: Suicide is a worldwide growing but neglected problem crossing culture, geographies, religious, social and economic boundaries. Suicide is a perplexing phenomenon of taking one’s own life. As versatile human beings are, reasons behind suicide attempts are also unique. There is paucity of study on the clinical characteristics of these patients from a psychosocial and psychiatric point in Bangladesh.Objective: The study was aimed to assess the socio-demographic profile and psychiatric morbidity in attempted suicide patients.Methods: This cross-sectional observational study was carried out for 4 months (May’2017-September’2017) at the Rangpur Medical College Hospital, Rangpur, Bangladesh. ). A total of 101 patients were purposively selected from the patients with suicidal attempt from different departments of the hospital (Medicine, Surgery, Head-Neck & Otorhinolaryngology). Informed written consent was obtained from all patients. The interview was conducted once the patient was considered fit for a psychosocial assessment using a semi-structured questionnaire and clinical interviews. Diagnosis was made according to DSM-IV. Data was entered and analyzed using SPSS version 24 and results were expressed as proportions and percentages.Results: The majority of suicide attempts seen are in socio-economically-deprived young persons. Majority were